アラタニ メイメイ サレタ ナンキョク チメイ - 国立極地研究所; コクリツキョクチケンキュウショ; National Institute of Polar Research (国立極地研究所, 1979)
P(論文) 1979年3月22日,南極地域観測統合推進本部の総会において,南極地名委員会選定の原案が審議され,以下の41の地名が新たに命名された. The Antarctic Place-Names Committee of Japan worked out 41 new place names, which were officially approved by the Japanese Antarctic Research EX-pedition Headquarters, under date of 22nd March 1979. departmental bulletin paper